Development of geography alternative assessment module for Malaysia secondary school - Hanifah Mahat,; Nasir Nayan,; Yazid Saleh,; Muhammad Hariz Muhamad Adnan,; Nuraini Sawal,; Saiyidatina Balkhis Norkhaidi, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study aimed to develop an Alternative Assessment Module, evaluate the validity of its contents, and test its applicability in the teaching and learning sessions of Geography teachers in Malaysia for Form One topics. The Design and Development Research (DDR) approach was used to develope the module, complimented by a survey to elicit feedback on its content validity and applicability among Form One Geography teachers. The needs analysis involved interviews and document analysis to design a draft of the Alternative Assessment Module. The interview method included three Geography teachers with over ten years of teaching experience, while the document analysis method focused on Form One’s Geography Standard Document for Curriculum and Assessment (DSKP) and the Classroom Assessment Handbook. A survey was conducted using a purposive sampling method, involving five experts from various fields to assess the module’s validity and six Geography teachers from three schools in the Hulu Selangor district in Selangor to evaluate its applicability. The study findings indicated that the module’s content validity, as measured by the coefficient value, was 0.85. Additionally, the module’s applicability in teaching was found to be high in terms of effectiveness (M = 4.7, SD = 0.21), efficiency (M = 4.2, SD= 0.34), and satisfaction (M = 4.7, SD = 0.23). The study concluded that the Alternative Assessment Module can be effectively used as one of the teaching resources for Classroom Assessment. The implications of this study highlight the focus on teachers’ achievement of learning objectives for the topic of drainage in Malaysia using the Alternative Assessment Module.